Hypocomplementemia as a Risk Factor for Organ Damage Accrual in Patients with Systemic Lupus Erythematosus. (30th December 2018) - Raymond, Warren; Eilertsen, Gro; Nossent, Johannes
Abstract : While it is a common practice to monitor complement levels in patients with systemic lupus erythematosus to aid in flare prediction and detection, it is unclear if this strategy is helpful in preventing subsequent organ damage. We studied longitudinal complement levels in 102 SLE patients during a median follow-up of 13.8 years (IQR 7.0, 23.1). Low complement was defined as C3 < 0.84 g/L and/or C4 < 0.08 g/L, disease activity by clinical SLEDAI-2K, and organ damage by SLICC-DI. We calculated a time averaged clinical SLEDAI score (cWAS) and performed multivariate regression models to assess the independent predictive value of low complement for organ damage at last visit. Hypocomplementemia (HC) was observed in 67% of all patients and was more often due to low C3 (97%) than low C4 (54%). Compared to patients not developing HC (33%), HC patients were more frequently positive for anti-dsDNA Ab (72% vs 36%, p < 0.01 ) and aPL (74% vs 40%, p < 0.01 ) but HC was concurrently present with anti-dsDNA Ab in only half the cases. The time-adjusted cWAS scores (1.9 vs 1.2, p = 0.9 ), frequency (SDI > 0, n = 60 ), and type of organ damage accrual were similar for patients with and without HC (OR 1.08, p > 0.20 ). Intermittent or sustained HC has no predictive value for damage accrual in SLE or the underlying disease activity over time. This together with significant discrepancies in the concurrence of low C3, C4, and anti-dsDNA Ab indicates frequent activation of the complement pathway by other factors than immune complexes in SLE.